A Sixth-century Story in a Nineth-century Tract? Torna, torna, frater Revisited - Negrău, Elisabeta (Studia Ceranea, 2024)
This article focuses on the Latin words torna and frater. According to the accounts of Theophylact Simocatta and Theophanes the Confessor, the words were used by soldiers participating in the Byzantine-Avar war campaign in the Haemus mountains in 587. Relying mainly on the passage from the chronicle of Theophanes, Romanian scholars have interpreted the words as an early form of a Balkan Romance idiom spoken by the local population. The two words would not be strong enough evidence to support the view that this is a sample of early Balkan Romance language in the sixth-century Thrace. The analysis of the words, as well as of the context in which they were used, links the phrase “torna, torna, frater” to Vulgar Latin and sermo castrensis. The author also argues that the chroniclers dramatized the accounts of the episode where the words were used. Additionally, the form fratre, which is found in two manuscript copies from the eleventh and twelfth centuries, seems to be an interpolation from a medieval Western Romance language, likely early Italian, and should not be identified with any language used in the Balkans. “Torna torna fratre” should be viewed as indicating a grasp of Italianate Latin within the Middle Byzantine context. This view contradicts the earlier assertions on the subject.